HUBUNGAN FUNGSI GINJAL, KALSIUM, DAN FOSFOR DENGAN XEROSIS DAN PRURITUS PADA PASIEN YANG MENJALANI HEMODIALISIS (Media Dermato Venereologica Indonesiana, 2020)
Pruritus and xerotic skin often accompany patients with chronic kidney disease (CKD) and have no clear pathophysiology. Hypercalcemia, hyperphosphatemia, and uremia might play a role in the development of pruritus. A descriptive study with a cross-sectional study design was conducted on 39 patients at the Hemodialysis Unit of Atma Jaya Hospital in August 2019. The degrees of pruritus and xerosis were assessed by the 5-D Pruritus Scale and Overall Dry Skin score (ODS). Blood urea, creatinine, calcium, and phosphorus levels were examined to determine their relationship to pruritus and xerosis using linear regression. All patients in this study had xerotic skin, with an incidence of pruritus of 46.2%. A decline in creatinine level was associated with a higher pruritus score. It indicated that a decrease in creatinine level was associated with an increase in pruritus scores (β = -0.658; p <0.05). There was a significant positive association between phosphorus levels with pruritus and xerosis scores (β = 1.44; p <0.05; β = 0.282; p <0.05). We did not find any significant relationship between ureum and calcium with the degree of pruritus and xerosis.